Falls in long-term care institutions for elderly people: protocol validation - Cristina Rosa Soares Lavareda Baixinho; Maria dos Anjos Coelho Rodrigues Dixe; Maria Adriana Pereira Henriques
ABSTRACT Objectives: To validate the content of a fall management risk protocol in long-term institutions for elderly people. Methods: Methodological, quanti-qualitative study using the Delphi technique. The tool, based on the literature, was sent electronically to obtain consensus among the 14 experts that meet the defined inclusion criteria. Results: The 27 indicators of the protocol are organized in three dimensions: prepare for the institutionalization (IRA=.88); manage the risk of falls throughout the institutionalization (IRA=.9); and lead the communication and formation (IRA=1), with a CVI=.91. Two rounds were performed to get a consensus superior to 80% in every item. Conclusion: The values obtained in the reliability test (>0.8) show that the protocol can be used to meet the intended goal. The next step is the clinic validation of the protocol with residents of long-term care institutions for elderly people.